The Anglican Eucharist in Australia's Beginnings. (September 2022) - Douglas, Brian
This article examines the beginnings of the Eucharist in Australia with the coming of the First Fleet of military and convict settlers in 1788. The role of the first Chaplain, the Rev'd Richard Johnson, is examined against his evangelical background. Tentative suggestions of sacramentality are made within the rich mixture of religious understandings in Australia, including those of the British government and its officials, concerning the Eucharist. The coming of a later ecclesiastical hierarchy in the form of archdeacons and bishops is also discussed to show the emerging influence of the Oxford Movement on eucharistic theology in early Australia, together with continuing evangelical influence.